Ticket War Konser Coldplay dan Fenomena Fear of Missing Out - Patria, Febe Agustin; Zulfiningrum, Rahmawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Coldplay, as one of the most popular bands in the world, is often the center of attention of global music fans. Their concerts are considered unforgettable experiences, and tickets are often a rarity. This research uses Self Determination Theory which includes autonomy, competence and connectedness, aiming to analyze the influence of FOMO (Fear of Missing Out) on the competition for tickets to the 2023 Coldplay concert. Phenomenology is used to find out how FOMO is among Coldplay’s fans with the points Edited Content, Continuous Update , Social Comparison, Comments & Likes, Events & Social Invitations. This research uses a qualitative approach by conducting interviews, observation and documentation. The research results show FOMO behavior among Coldplay fans; 1) Autonomy, watching concerts is a personal desire; 2) Competence, a Coldplay concert is considered an achievement, creating satisfaction; 3) Connectedness, increasing motivation to get involved in the concert. Media content influences feelings of FOMO. Social media algorithms make it easier to access information. Social comparison triggers feelings of envy, but people's success in getting tickets through events & social invitations does not affect feelings of FOMO. FOMO and the influence of social media encourage people to get involved in Coldplay concerts, thus creating satisfaction. When individuals are in a missing out situation, some of them experience disappointment, but others respond to these feelings by diverting their disappointment into positive things.